The Relationship Between Eating Habits and Body Mass Index of Adolescent Students Doing Sports: Eating Habits BMI Adolescent - Çıplak, Mustafa Ertuğrul; Eler, Nebahat (Progress in Nutrition, 2020)
Background: Evaluation of nutritional and eating habits is important for the development of healthy and quality life and nutrition education in all individuals. Aim: In this study, it was aimed to determine the relationship between eating habits and body mass index values of students playing in school teams. Materials and Methods:  A total of 110 students who are in primary school with participating competitions in 10-14 age group school teams. Age, and BMI (calculated with height and body weight values) ​​of the students, and eating habits test questionnaire was applied. SPSS 20 software was used to analyze the data. Independent t-test was used to determine the difference between eating habits of male and female students, and correlation coefficient analysis was applied to examine the differences between nutritional habits and BMI in order to determine their respective differences. Results: Mean height (cm) of the females was 143.4±1.70 and 145.5±2.64 in males, mean body weight (kg) was determined as 38.11±1.49 in females and 40.81±1.87 in males. In this study, mean body mass index values (kg/m2) was found as 19.16±0.41 for females and 18.83±0.42 for males. The mean score of eating habits was stated as 101.39 for males and 99.76 for females but there was no statistically significant relationship between eating habits nor gender neither BMI (p>0.05). Conclusions: As a result, no statistically significant relation was found between eating habits and body mass index of the students and between eating habits and gender. We think that the majority of students have neutral eating habits, that is, they practice healthy eating habits in the same way as unhealthy eating habits.